The Implementation of Integrity Learning Through Entrepreneurship Activities and Anti-Corruption Behavior - Hayati, Hayati; Mayasari, Eka (Jurnal Ilmiah Peuradeun, 2019)
This research aims to develop the values of integrity ​​through Entrepreneurship in fostering independent spirit and anti-corruption behavior in students of Serambi Mekkah University students Banda Aceh. The design of this study was carried out in two stages. In the first stage a survey was conducted on the methods and approaches used as input in developing Integrity learning methods by using Entrepreneurship approach involving students and lecturers. In the second stage, a trial was conducted on the development of Entrepreneurship learning in the field by involving students and lecturers. The research method used in this study was the approach (mix method). The population of this study was all students of Serambi Mekkah University consisting of 8 Faculties, approximately (2000 students), the author took 10% of the population to be sampled from 8 Faculties, consisting of 200 students. The results of the study found that not all study programs at Serambi Mekkah University applied Integrity and Entrepreneurship courses, integrity and entrepreneurship subject lecturers did not fit the background of their respective expertise.